Technological extension actions in the development of an environmental project: challenges and experiences - Silva, Carmem Cícera Maria da; Lima Barbosa, Gabriela; Salles, Davi Cardoso; Nascimento, Sofia Andrade; Elias, Yohana de Freitas; Céleri, Eliomar Pivante; Lacerda Junior, Valdemar (Brazilian Journal of Production Engineering, 2024)
According to CONSEX Resolution no. 10/2020, technological extension is an activity that, integrated with teaching and research, assists in the development, improvement, and dissemination of scientific and technological solutions. This experience report aimed to present experiences lived and strategies used in the execution of technological extension in the environmental and biofuels area. During the execution of technological extension actions, activities outside the university were carried out, providing different experiences for undergraduate and graduate students, as well as professors. A partnership was formed with a private company from Espírito Santo state, and an account was created on a highly influential social media platform. The purpose was to share the planned and executed actions of the project throughout its implementation, aiming to reach a diverse audience. Daily posts aimed to promote environmental awareness, a key aspect of this technological extension project. External events were held at higher education institutions, primary schools (grades 1 to 6), childcare centers, and typical gastronomic artisan fairs in the region of Espírito Santo. Perceptions and results varied according to the local audience, with primary schools showing the highest interest.